India - Singh, Sarina; Bindloss, Joe (Fort Mill : Lonely Planet, 2011)
Lonely Planet's India is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Explore the magnificent monument to love that is the Taj Mahal, climb into the high Hima.
Keywords: Lonely Planet -- Non-fiction; Travel guide -- Non-fiction